Pengaruh Intellectual Capital Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Intervening - Atikah Juliani Putri; Henri Agustin; Nayang Helmayunita (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to determine the effect of intellectual capital on firm value and profitability as an intervening variable. This research was conducted on finance companies listed on the Indonesia stock exchange in 2013-2017. The sample is determined by purposive sampling 48 finance companies are obtained. Technique of collecting data is done by documentation technique obtained through IDX official website: www.idx.co.id. Data analysis used is structural equation modeling (SEM) using SmartPLS software ver 3.2.7. The result of the research shows that (1) the intellectual capital positive effect on the firm value (2) the intellectual capital does no effect the firm value through profitability